Factors controlling the pluripotent state of human embryonic stem cells - del Pilar Vazquez Arango, M (2012)
In the field of regenerative medicine, human embryonic stem (hES) cells offer the potential to treat degenerative diseases and replace damaged or non-functional tissue. However, it is not fully clear how hES cells retain a pluripotent state or differentiate into specific cell lineages. Although most of previous research has found that various proteins are responsible for the balance in hES cell maintenance and differentiation, there is mounting evidence for non-coding RNAs as important players in this task. Data from our laboratory shows that there are genes that encode for variants of the non-coding RNA U1 small nuclear (sn)RNA, a key component of the spliceosome. These variant (v)U1 snRNA genes are transcriptionally active and differentially expressed. Moreover, interfering with the activity of a specific vU1 snRNA affects the expression of a subset of genes at the level of pre-mRNA 3' end processing (O'Reilly et al., 2012). I have analysed the expression of vU1 snRNA genes throughout hES cell differentiation and shown that vU1 snRNA genes are down regulated upon differentiation into macrophages. Interestingly, analyses of steady state levels of specific vU1 snRNAs throughout hES cell differentiation revealed a characteristic pattern where specific vU1 snRNAs are more stable in the final differentiation step (i.e. macrophages). Thus, strongly supporting the idea that the vU1 snRNA genes are being regulated throughout differentiation both at the level of transcription and snRNA stability. Furthermore, vU1 snRNAs are up regulated upon reprogramming of primary human skin fibroblasts into induced pluripotent stem (iPS) cells, whose pattern of expression is similar to hES cells. Therefore, we hypothesize that vU1 snRNAs play a significant role in establishing pluripotent stem cells and that their differential expression may be key during development and cell reprogramming.